Significant role of Psf3 expression in non‐small‐cell lung cancer. Issue 11 (7th October 2015) - Tane, Shinya; Sakai, Yasuhiro; Hokka, Daisuke; Okuma, Hiromichi; Ogawa, Hiroyuki; Tanaka, Yugo; Uchino, Kazuya; Nishio, Wataru; Yoshimura, Masahiro; Maniwa, Yoshimasa
Abstract : The GINS complex associates with cell division cycle (Cdc) protein 45 and mini‐chromosome maintenance (Mcm) proteins 2–7 to form the Cdc45–Mcm–GINS (CMG) complex, which is essential for DNA duplication. One member of the GINS complex is Psf3. We previously found that increased Psf3 expression was strongly associated with poor survival in lung adenocarcinoma. Here, we investigated the role of Psf3 expression in non‐small‐cell lung cancer (NSCLC). We verified Psf3 expression in human NSCLC tissues (180 patients) and cell lines. Immunohistochemical analysis revealed that the overexpression of Psf3 was significantly associated with vessel invasion ( P = 0.016), lymphatic invasion ( P = 0.002), and pleural invasion ( P = 0.036). The overall survival rate in patients with Psf3 overexpression was significantly lower than that in patients without Psf3 overexpression ( P = 0.006). Multivariate survival analysis revealed Psf3 expression to be an independent risk factor for an unfavorable outcome ( P = 0.049). A proximal ligation assay showed interactions between Psf3 and other CMG components (such as Mcm2 and Cdc45) in both NSCLC specimens and cell lines, indicating that Psf3 acted as the CMG complex, which could lead to excessive proliferation. Knockdown of Psf3 inhibited the proliferation of both cell lines by delaying the S phase, which revealed that Psf3 played an important role in cancer proliferation. Thus, Psf3 acted as the CMG complex, promoting excessive proliferation. These results suggest that Psf3 inhibition might be a therapeutic target for NSCLC with Psf3 overexpression. Abstract : Our investigation of surgically resected specimens from patients with non‐small‐cell lung cancer (NSCLC) revealed that Psf3 expression was strongly correlated with tumor progression in NSCLC. Moreover, Psf3 acted as the CMG complex, which could lead to excessive proliferation. These findings provide clues regarding the role of Psf3 in NSCLC, and could yield novel molecular‐targeted treatment strategies aimed at inhibiting the pathways that lead to the proliferation and progression of NSCLC.